Strategies to develop French pronunciation using virelangue - Dewa, Ayu Nastiti; Laksman-Huntley, Myrna (Diksi, 2022)
This article examines the effectiveness of virelangue as a strategy to overcome phonetic interference in beginners who have never studied French. This case study qualitative research used pre-test and post-test strategies to see the development of pronunciation from each trial, then analyzed the tests results using the theories of phonetics and phonology by Léon (1993) and Chaer (2009), the analysis of language errors by Tarigan & Tarigan (2011), and the theory of interference by Weinreich (2011). The results indicate that there is interference called phonetic treatment of borrowed words. The most difficult sounds to pronounce are [É›Ìƒ] and [Ê’]. Due to the limited knowledge of the research subjects, there is also hypercorrection. During these trials, there is a development of pronunciation that improved the research subjects accomplishment from average to outstanding. Asian language studies students, learning more difficult sounds, were the only group pronouncing the virelangue correctly in the last trial. Keywords: virelangue, reading aloud, phonetics, interference, pronunciation